Refleksi Internasionalisasi Bahasa Indonesia Melalui BIPA: Analisis Kohesi dan Koherensi - Irianto, Deni Nugroho (Crises on Languages and Literature, 2025)
The issue of how grammatical cohesion and coherence can influence the clarity and fluency of communication in the seminar trigger the author to conduct this research. The purpose of this study is to investigate how linguistic elements play a role in creating coherent and cohesive discourse, especially in the context of language learning by foreign speakers. The research was conducted using descriptive analysis and a qualitative approach. Data were collected from seminar videos uploaded to the YouTube channel of the Faculty of Cultural Sciences, UGM. The videos were transcribed and analyzed using linguistic theory, specifically cohesion and coherence theory. Data were collected through free-listening observation, where the researcher observed and recorded language use without directly participating in the communication process. The results of the study show that grammatical cohesion in the seminar discourse was achieved through the use of conjunctions, references, substitutions, and ellipsis. Coherence was achieved through logical relationships between the ideas presented by the seminar participants, including additive and causal relationships. This analysis provides insights into the importance of cohesion and coherence in creating effective and well-understood communication among foreign language learners.